Mali : Request for Three-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Mali's Request for Three-Year Arrangement Under the Extended Credit Facility (ECF). The economic outlook for Mali remains positive; however, subject to important downside risks. The potential real growth rate is estimated at about 5 percent per year and inflation is expected to continue to be contained by the CFAF's peg to the euro. Downside risks relate to the possible further deterioration of the security situation, potential shocks to the terms of trade (the price of gold, cotton, and fuels), and adverse weather conditions. Going forward, it is essential to pursue greater spending efficiency, including through strengthened project selection and execution, as well as the rationalization of subsidies. The authorities' efforts to increase financial inclusion and narrow the gender gap, including by direct measures to economically empower women are welcome. The new ECF arrangement aims to support the authorities' development strategy (CREDD) for strong and inclusive growth through job creation, economic diversification, and greater resiliency. The main focus in the short term is to significantly increase revenue collection to allow for development spending and to reform the energy sector.